OPTIMASI FORMULASI SABUN PEMBERSIH WAJAH ANTIBAKTERI VARIASI KOMBINASI MINYAK ATSIRI KULIT JERUK DAN EKSTRAK DAUN KEMANGI - Gigih Kenanga Sari; Estuningtyas Ayu Hapsari (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Background: orange peel essential oil and basil leaf extract are known as natural ingredients that contain medicinal ingredients. The extracts of these two plants are useful as antibacterials. Objective: to determine the antibacterial activity of facial soap containing the active ingredients orange peel essential oil and basil leaf extract. The methods studied include: organoleptic properties, pH value, foam height, free alkali content, specific gravity and antibacterial activity. The type of research used is experimental research. Data collection was carried out by measuring, while data analysis was descriptive and analytical. The research design used was a post-test only control design. Conclusions include the preparation of facial cleansing soap with a combination of orange peel essential oil and basil leaf extract which meets SNI requirements which is classified as an inhibitory bacterial work zone but the most optimal is F3, there are differences in the diameter of the inhibitory zone for the growth of Staphylococcus aureus bacteria in facial cleansing soap with a combination of active ingredients. orange peel essential oil and basil leaf extract.